Tạo cá bảy màu poecilia reticulata cái có bộ nhiễm sắc thể giới tính XY và nhận dạng cá bảy màu siêu đực YY - Lâm, Minh Trí (Bộ Giáo dục và Đào tạo, 2013)
Gravid guppy females were orally administered estrogens estradiol propionat (EP) or ethynylestradiol (EE) 5-10 days prior parturition. Treatment with 400ppm of EP and 250 ppm of EE caused the birth of 91.03± 2.37% and 91.02% females respectively. F2 progeny from the sex reversal females XY and norman males XY consisted of 69.13% male, among which 14.25% were identified as superrnales YY. Some morphological traits determined by X - or Y - linked gens were investigated to indentify XY female, XX male and YY supermale.